Odpowiedzi

Najlepsza Odpowiedź!
2009-05-23T22:49:34+02:00
Rozwiąż układ równań

x2 - y2 = 0
y - 2x = 1

x2=y2
y - 2x = 1

x=y
x-2x=1

x=-1
y=-1


metodą przeciwnych współczynników

3x + 2y = 1
2x + 4y = -4 /*(-1)

3x + 2y = 1
-2x - 4y = 4 /:2

3x + 2y = 1
-x - 2y = 2

2x=3
x=1,5

x=1,5
y=1,75


Metodą podstawiania

3x - y = 1
2x + 5y = 12

y = -1+3x
2x + 5y = 12

y = -1+3x
2x + 5(-1+3x) = 12

y = -1+3x
2x -5+15x = 12

y = -1+3x
17x = 17

y = -1+3=2
x = 1
  • Użytkownik Zadane
2009-05-23T22:51:33+02:00
2.
3x+2y=1 //*(-2)
2x+4y=-4

-6x-4y=-2
+ 2x+4y=-4
-4x=-6//:(-4)
x=24
3*24+2y=1
2y=1-72
2y=-71//:2
y=35,5

x=24
y=35,5

3.
3x-y=1
2x+5y=12

3x-1=y

2x+5(3x-1)=12
2x+15x-5=12
17x=17//:17
x=1

3*1-y=1
3-1=y
y=2

x=1
y=2





  • Użytkownik Zadane
2009-05-23T22:57:15+02:00
Metoda przeciwnych współczynników

3x + 2y = 1 /*(-2)
2x + 4y = -4

-6x - 4y = -2
2x + 4y = -4

-4x = -6
x = 1,5

y = 1/2 - 3/2x
y = 0,5 - 2,25
y = -1,75

Metoda podstawiania:
3x - y = 1
2x + 5y = 12

y = 3x - 1
2x + 5(3x - 1) = 12

y = 3x - 1
2x + 15x - 5 = 12

y = 3x - 1
17x = 17

x = 1
y = 3*1 - 1

x = 1
y = 2


Trzeci układ:
x² - y² = 0
y - 2x = 1

y = 2x + 1
x² - (2x + 1)² = 0

x² - (4x² + 4x + 1) = 0
x² - 4x² - 4x - 1 = 0
-3x² - 4x - 1 = 0

Δ = (-4)² - 4 * (-3) * (-1) = 16 - 12 = 4
√Δ = 2
x1 = (4 + 2) / -6 = -1
x2 = (4 - 2) / -6 = -1/3

y1 = -2 + 1 = -1
y2 = -2/3 + 1 = 1/3